Energy dissipation mechanism and damage model of marble failure under two stress paths (Fracture and Structural Integrity, 2014)
Marble conventional triaxial loading and unloading failure testing research is carried out to analyze the elastic strain energy and dissipated strain energy evolutionary characteristics of the marble deformation process. The study results show that the change rates of dissipated strain energy are essentially the same in compaction and elastic stages, while the change rate of dissipated strain energy in the plastic segment shows a linear increase, so that the maximum sharp point of the change rate of dissipated strain energy is the failure point. The change rate of dissipated strain energy will increase during unloading confining pressure, and a small sharp point of change rate of dissipated strain energy also appears at the unloading point. The damage variable is defined to analyze the change law of failure variable over strain. In the loading test, the damage variable growth rate is first rapid then slow as a gradual process, while in the unloading test, a sudden increase appears in the damage variable before reaching the rock peak strength. According to the deterioration law of damage and the impact of confining pressure on the elastic modulus, a rock damage constitutive model is established, which has a better fitting effect on the data in the loading and unloading failure processes.
Keywords: Energy evolution